기술 준비도와 소비자 준비도가 Self Service Technology 사용동기와 태도 및 사용의도에 미치는 영향 - 심현숙(Hyeon Sook Shim); 한상린(Sang Lin Han) (Asia Marketing Journal (Online), 2012)
Researches about the relationship between SST(Self Service Technology) and TRI(Technology Readiness Index) have been carried out after TRI was developed by Parasuraman and his colleagues(2000). We hypothesize Consumer Readiness can also influence consumer's motivation, attitude, and intent to use SST. Currently, there has been no research on this subject. In this study, we investigated the relationship between TR, Consumer Readiness and SST Core Attitudinal Model which Dabholkar & Bagozzi(1994) proposed. The researchers also investigated moderating effects of consumer traits and situational factors to verify the acceptance of such forms of service delivery by all kinds of consumers and under different situational contexts. Self consciousness, the need for interaction with an employee, and the technology anxiety were used as consumer trait variables. Perceived waiting time and perceived crowding were used as situational variables. 380 questionnaires were distributed to a sample group of people in their 20's and 30's, and the data were analyzed with structural equation model using AMOS 18.0 program. All of Cronbach's alpha values representing reliabilities were satisfactory. The values of Composite Reliability(CR) and Average Variance Extracted(AVE) also showed the above criteria, thus providing evidence of convergent validity. To confirm discriminant validity among the constructs, confirmatory factor analysis and correlations among all the variables were examined. The results were satisfactory. The results of this study are summarized as follows. 1. Optimism and innovativeness of TR partially influenced the motivation to use SST. People who tend to be optimistic use SST because of ease of use and fun. The innovative however, usually use SST due to its performance. However, consumer readiness of role clarity, ability and self-efficacy influence all the components of motivation to use SST, ease of use, performance and fun. The relative effect of consumer readiness on the motivation to use SST was much stronger and more significant than that of TR. No other previous studies have examined the effects of Consumer Readiness on SST usage motivation, attitude and intention. It is academically meaningful that the researchers verified that Consumer Readiness is the important precedent construct influencing the self service technology core Attitudinal Model. Our findings suggest that marketers should consider fun and ease of use attributes to promote the use of self service technology. In addition, the SST usage frequency will rise rapidly when role clarity, ability, and self-efficacy which anybody can easily handle SST is assured. If the SST usage rate is increased, waiting times for customers could be decreased. Shorter waiting time could lead to higher customer satisfaction. It may also result in making a long-term profit owing to the reduced number of employees. Thus, presentation of using SST by employees or videos showing how to use it will promote the usage attitude and intent. 2. In SST core attitudinal model, performance and fun factors among SST usage motivation affected attitudes of using SST. The attitude of using SST highly influenced intent to use SST. This result is consistent with previous researches that dealt with the relationship between motivation, attitude and intention. Expectation of using SST could result in good performance just like the effect of ordering menu to service employees and to have fun since fun during its use could promote more SST usage rate. 3. In the relationship among motivation, attitude and intent in SST core attitudinal model, the moderating effect of consumer traits(self-consciousness, need for interaction with service employees and technology anxiety) and situational factors(perceived crowding and perceived waiting time) were tested. The results also supported the hypothesized moderating effects except perceived crowding. The highly self-conscious tended to form attitudes to use SST because o 정보기술의 활용이 마케팅 전략의 중요한 부분으로 부각되는 시장 환경에서 본 논문에서는 패스트푸드 레스토랑에서 주문시 Self Service Technology(SST)를 사용 할 때 기술준비도와 소비자 준비도에 따른 사용동기, 태도, 사용의도의 차이를 검증하고자 하였다. Parasuraman이 TRI를 개발한 이후 SST와 TRI를 접목한 연구가 이루어져 왔지만 여전히 부족한 실정이다. 소비자 준비도 역시 SST사용에 대한 소비자의 동기와 태도 및 의도와 직접적인 영향을 미칠 수 있지만 이에 대한 연구는 이루어지지 않았다. 이에 본 연구에서는 패스트푸드 레스토랑에서 터치스크린 SST를 도입함에 있어 소비자의 기술준비도와 소비자 준비도가 Dabholkar & Bagozzi(1994)가 제안한 SST 핵심태도모델에 미치는 영향을 고찰하였다. 이때 모든 소비자와 상황적 요인에 따른 차이를 파악하고자 자아의식, 상호작용욕구, 기술에 대한 두려움 등의 소비자특성과 지각된 대기시간, 지각된 과밀 등의 상황적 요인에 따른 조절 효과를 검증하였다. AMOS 18.0프로그램을 사용하여 구조방정식 모델로 분석하였고 연구 결과 기술준비도 중 낙관성은 사용용이성과 재미 동기에 유의한 영향을 미치는 것으로 나타났다. 혁신성은 사용용이성과 성과에 유의한 영향을 미치는 것으로 나타났다. 역할의 명확성, 능력 및 자아 효능감으로 구성된 소비자준비도는 사용용이성, 성과와 재미 등 모든 SST사용동기 요소에 기술준비도보다 강하고 유의한 영향을 미치는 것으로 나타났다. 마지막으로 SST 핵심태도모델 내의 SST 사용 동기, 사용 태도 및 사용의도 간의 관계에서 소비자 특성과 상황적 요인의 조절효과를 검증한 결과 지각된 과밀을 제외한 모든 변수들이 조절효과를 지니는 것으로 나타났다. 이러한 연구 결과를 바탕으로 터치스크린 SST를 도입하려는 기업에 실무적 제언을 하였다.